KEY CONCEPTS IN ANATOMY AND PATHOLOGY THAT MEDICAL STUDENTS SHOULD MASTER (Modern education and development, 2025)
This paper outlines the core knowledge and skills that medical students must acquire in the subjects of anatomy and pathology. These foundational disciplines form the basis for clinical diagnosis, surgical precision, and understanding the mechanisms of disease. Mastery of both normal and pathological anatomy is essential for the development of competent medical professionals.